Penerapan Senam Brain Gym Sebagai Strategi Meningkatkan Perkembangan Motorik Halus Anak Usia Dini - Akhmadi Putro Aji Pangestu; David Triatna; Nur Cahyati Ngaisah (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2026)
Simple movements in the Brain Gym application are a new innovation in stimulating fine motor skills in early childhood, which previously tended to use sheets of paper for writing, thickening, drawing, and other activities. The purpose of this study was to create an interesting and fun strategy to hone children's fine motor skills through coordinated movements in Brain Gym activities. Data were obtained through qualitative methods with children aged 5-6 years at Dharma Wanita Dhawu Kindergarten using observation, documentation, and interviews. The data analysis technique in this study used the Miles and Huberman model with data analysis stages: data reduction, data presentation, drawing conclusions, and verification with data validity testing using triangulation techniques. The findings of this study indicate that strategies for developing fine motor skills in children aged 5-6 years can be implemented through Brain Gym activities, which are carried out in two ways: 1) using media that are fun and interesting for children, and 2) without using media that encourage children to move more actively.